Impactos do repasse do ICMS sobre a proficiência dos alunos do Estado do Ceará - uma medida do IQE - Teixeira, Anna Márcia Cordeiro (2015)
This paper aims to measure the impact of Municipal Index of Educational Quality - IEQ and the Municipal Human Development Index - MHDI of Ceará municipalities on the proficiency of students in 5 and 9 years of basic education of public schools of Ceará in Prova Brasil Exam, for the year 2011. The data source used for variables representing Brazil Support was extracted from the National Institute of Educational Studies Teixeira (INEP) for the year 2011. As for the MHDI was extracted from the United Nations Program United Nations Development Programme (UNDP), for the years 2010 and 2011 and the IEQ from the Institute for Economic Strategy Research of the State of Ceará (IPECE) for the IEQ, for the years 2010 and 2011. Using the method of Ordinary Least Squares stimations were made which indicated that proficiency in the subjects of Portuguese and Math for only the 5th year of basic education of public schools Ceará is better the higher the IDHM. And more importantly, the existence of asymmetries in the impact of IQE about student proficiency in math and Portuguese for two school years analyzed. Being students of the 5th year the most benefit